Job demands, organizational justice, and emotional exhaustion in prison officers - Clements, Andrew James (Criminal justice studies, 2021)
Prison officers experience a number of occupational and organizational stressors, and are at considerable risk of burnout. There has been limited research examining the processes by which the demands officers experience impact on their burnout risk. Drawing on the job demands-resources model, we tested distributive justice perceptions as a mediator for the relationship between workload and violence with emotional exhaustion. We further tested whether supervisor-focused interactional justice perceptions would be associated with reduced emotional exhaustion via stress culture (i.e. a perceived ability to discuss stress-related problems with managers). UK prison officers (N = 1792) completed an online survey. Findings indicated that, while workload was associated with emotional exhaustion directly and via distributive justice, experiences of violence was only directly linked with emotional exhaustion. Interactional justice was significantly associated with emotional exhaustion via the ability to discuss stress-related problems, but the association was weak. Findings suggest positive manager-subordinate relationships are not sufficient to meaningfully enhance psychological wellbeing. Instead we highlight the need to manage officers’ workload.